Edward S. Corwin's Constitution and What It Means Today : 1978 Edition. - Corwin, Edward S. (Edward Samuel), 1878-1963 (Princeton University Press, 2001)
For over seventy-five years Edward S. Corwin's text has been a basic reference in the study of U.S. Constitutional Law. The 14th edition, the first new edition since 1973, brings the volume up to date through 1977. In this classic work, historian Edward Corwin presented the text of the U.S. Constitution along with his own commentary on its articles, sections, clauses, and amendments. Corwin was a renowned authority on constitutional law and jurisprudence, and was hired at Princeton University by Woodrow Wilson in 1905. Far from being an impersonal textbook, Corwin's edition was full of opinion.